Testing tidal theory for evolved stars by using red giant binaries observed by Kepler. (28th June 2018) - Beck, P G; Mathis, S; Gallet, F; Charbonnel, C; Benbakoura, M; García, R A; do Nascimento, J-D
Abstract: Tidal interaction governs the redistribution of angular momentum in close binary stars and planetary systems and determines the systems evolution towards the possible equilibrium state. Turbulent friction acting on the equilibrium tide in the convective envelope of low-mass stars is known to have a strong impact on this exchange of angular momentum in binaries. Moreover, theoretical modelling in recent literature as well as presented in this paper suggests that the dissipation of the dynamical tide, constituted of tidal inertial waves propagating in the convective envelope, is weak compared to the dissipation of the equilibrium tide during the red giant phase. This prediction is confirmed when we apply the equilibrium-tide formalism developed by Zahn, Verbunt & Phinney, and Remus, Mathis & Zahn on to the sample of all known red giant binaries observed by the NASA Kepler mission. Moreover, the observations are adequately explained by only invoking the equilibrium tide dissipation. Such ensemble analysis also benefits from the seismic characterization of the oscillating components and surface rotation rates. Through asteroseismology, previous claims of the eccentricity as an evolutionary state diagnostic are discarded. This result is important for our understanding of the evolution of multiple star and planetary systems during advanced stages of stellar evolution.